Synchronous grouting material based on muddy silt shield muck and preparation method thereof
By using fine sand containing mud powder and specific additives in synchronous grouting materials and combining cement, the problems of poor fluidity, insufficient compressive strength and impermeability of synchronous grouting materials in the prior art are solved, and the material efficiency is achieved. Economic and environmentally friendly applications.
Patent Information
- Application Number
- CN202510054221.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing synchronous grouting materials have problems such as poor slurry fluidity, floating pipe sheets, and water leakage during construction, which is difficult to control quality and has high construction safety risks.
Synchronous grouting materials based on mud silt sandstone shield slag are used. The main raw materials are mud powder fine sand, combined with cement and specific additives (ethyl trimethylsilicate, disodium hydroxyethylphosphonate, aminotrimethylene Pentasodium phosphonate) improves compressive strength and impermeability through the synergistic effect between the components.
It effectively improves the flowability, compressive strength and permeability of synchronous grouting materials, reduces material costs, reduces waste transportation and disposal costs, and improves construction safety and economic benefits.
Smart Images

Figure CN119462024A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tunnel grouting materials, and more specifically, to a synchronous grouting material based on muddy silt shield slag and a preparation method thereof. Background Art
[0002] Synchronous grouting technology is an indispensable and key auxiliary method in shield tunneling. Synchronous grouting in shield excavation is an effective means to fill the construction gap between the segment lining and the stratum and reduce the subsequent soil deformation. It can enhance the stability of the tunnel and is the key to controlling surface settlement.
[0003] Synchronous grouting slurry is generally cement mortar, which is made of cement, sand, fly ash, bentonite and water in a certain proportion. The output of shield slag in urban subway construction is extremely abundant. If these resources can be effectively used to prepare synchronous grouting materials, it will produce huge economic, environmental and social benefits.
[0004] There are a series of problems in the synchronous grouting construction process, such as poor slurry fluidity, pipe segment floating, pipe segment water leakage, etc., which makes quality control difficult and the construction safety risk high. First of all, the floating of the pipe segment is mainly due to the long coagulation time of the slurry. The slurry is in a fluid state for a long time, which makes the buoyancy of the pipe segment greater than its own gravity, resulting in the floating of the pipe segment; secondly, the leakage of the pipe segment is largely due to the poor anti-seepage ability of the slurry, and groundwater penetrates into the tunnel from the gap behind the wall. At the same time, the slurry is required to have good fluidity during grouting. Because of good fluidity, the slurry pressure loss is small, so it can diffuse farther from the grouting point, making the slurry filling more full.
[0005] In order to solve the above problems, domestic and foreign scholars have conducted many studies. The traditional way to improve the fluidity of slurry is to add dispersants or water reducers to the slurry. Although the fluidity is improved, the strength of the slurry will be reduced. In addition, the cost of water reducers is very high and uneconomical. The traditional way to reduce the setting time of slurry is to add accelerators, but at the same time the fluidity of the slurry is reduced, making grouting construction extremely difficult.
[0006] Therefore, it is of great significance to develop a synchronous grouting material with strong flowability, good filling performance, strong anti-permeability, controllable setting time and strength, and economic and environmentally friendly. Summary of the invention
[0007] Based on the above-mentioned technical problems existing in the prior art, the present invention provides a synchronous grouting material based on muddy siltstone shield slag. The material takes muddy siltstone as the main raw material, replacing the bentonite and fine sand in the synchronous grouting in the prior art, and is combined with cement and specific additives. Through the synergistic effect of the components, the compressive strength and impermeability of the synchronous grouting material are effectively improved. At the same time, local materials can be used, and the cost of transporting and disposing of a large amount of slag is greatly reduced.
[0008] In order to achieve the above object, the technical solution of the present invention is as follows: A synchronous grouting material based on muddy siltstone shield slag, comprising the following components in parts by weight: 13-16 parts cement 16-20 parts of slag 142-147 parts of fine sand containing mud 0.03-0.1 part of trimethylsilyl acetate Etidronate disodium 0.07-0.17 parts Pentasodium aminotrimethylenephosphonate 0.03-0.1 parts 63-67 parts of water.
[0009] In some embodiments, the cement is ordinary Portland cement and / or sulphoaluminate cement.
[0010] In some embodiments, the density of the slag is 2.0-3.0 g / cm 3 ; Specific surface area is 350-500m 2 / kg.
[0011] In some embodiments, the particle size of the mud-containing fine sand is less than 2 mm, and the clay content is 20-30%.
[0012] In some embodiments, the mud-containing fine sand is particles with a particle size of less than 2 mm obtained after multiple screening of shield slag.
[0013] In some embodiments, shield tunneling debris is screened once to separate coarse particles larger than 6 mm and sand-containing mud smaller than 6 mm; the sand-containing mud smaller than 6 mm is then rinsed and screened twice to separate intermediate particles of 2-6 mm and sand-containing mud smaller than 2 mm; the sand-containing mud smaller than 2 mm is separated to obtain mud-containing fine sand and mud, and the mud-containing fine sand is collected.
[0014] The present invention also provides a method for preparing a synchronous grouting material based on muddy siltstone shield slag according to any of the above embodiments, the method comprising the following steps: (1) First, cement, slag, fine sand containing mud powder and part of water are mixed and stirred thoroughly to obtain a first slurry; (2) then mixing ethyl trimethylsilyl acetate with a portion of water and adding the mixture to the first slurry obtained in step (1) above and stirring the mixture thoroughly to obtain a second slurry; (3) mixing etidronate disodium with a portion of water and adding the mixture to the second slurry obtained in step (2) above, and stirring the mixture thoroughly to obtain a third slurry; (4) finally, pentasodium aminotrimethylenephosphonate and the remaining water are mixed and added to the third slurry obtained in the above step (3), and stirred thoroughly to obtain a synchronous grouting material; The entire stirring time of steps (1) to (4) is controlled within 5-10 minutes.
[0015] In some embodiments, the entire stirring time is controlled within 6-8 min.
[0016] The technical solution of the present invention, the interaction principle between the additive and each component is as follows: 1. The action and reaction mechanism of etidronate disodium
[0017] (1) Hydrolysis of etidronate disodium (C2H9Na2O7P2) (2) Promote the depolymerization of cement paste flocculation structure After cement is mixed with water, a double electrical layer structure is formed on the surface of the cement particles due to the hydration of the cement particles, forming a solvated water film. The surfaces of the cement particles carry opposite charges, which causes association between the cement particles, forming a flocculated structure in the cement slurry. 10% to 30% of the mixing water is wrapped in the cement particles and cannot participate in free flow and lubrication, thus affecting the fluidity of the cement slurry.
[0018] The -OH hydrophilic group produced by the hydrolysis of etidronate disodium (C2H9Na2O7P2) has nucleophilicity and can be adsorbed on the surface of cement particles in a directional manner, so that the surface of cement particles is negatively charged, forming an electrostatic repulsion effect, prompting the cement particles to disperse with each other, the flocculation structure of cement particles to disintegrate, and release part of the encapsulated water to participate in the flow, thereby effectively increasing the fluidity of the slurry. At the same time, the hydrophilic group has a strong polarity, so the hydrophilic group adsorption film on the surface of cement particles can form a stable solvated water film with water molecules. This water film can play a lubricating role, effectively reducing the sliding resistance between cement particles, thereby improving the fluidity of the slurry. (3) Chelation effect and accelerated hydration
[0019] The reactions during cement hydration are as follows: Tricalcium silicate hydration in cement: 2(3CaO·SiO 2 ) + 6H 2 O=3CaO·SiO 2 ·3H 2 O + 3Ca(OH) 2 Tricalcium silicate hydration in cement: 2(2CaO·SiO 2 ) + 4H 2O=3CaO·SiO 2 ·3H 2 O + Ca(OH) 2 Tricalcium aluminate hydration in cement: 3CaO·Al2O3 + 6H2O = 3CaO·Al2O 3· 6H2O 3CaO·Al2O3·6H2O + 3(Ca2SO4·2H2O) + 19H2O=3CaO·Al2O3·3Ca2SO4·31H2O Tetracalcium aluminoferrate hydration in cement: 4CaO·Al2O3·Fe2O3 + 7H2O = 3CaO·Al2O3·6H2O + CaO·Fe2O3·H2O The hydration product Ca(OH)2 produced by cement hydration ionizes a large amount of Ca 2+ The hydroxyl groups generated by the hydrolysis of etidronate disodium react with the Ca2+ generated by cement hydration. 2+ The formation of a six-ring chelate further accelerates the hydrolysis of Ca(OH)2, promotes the rapid hydration of cement, and exhibits an ideal early strengthening effect. The reaction principle is as follows: . 2. Mechanism of action of sodium amino trimethylene phosphonate
[0020] (1) Hydrolysis of sodium aminotrimethylenephosphonate The Na produced by hydrolysis of sodium aminotrimethylenephosphonate + OH generated by cement hydration — Combined with cement, it generates strongly alkaline NaOH, which reacts with SiO2 in the mud-containing fine sand to generate hydrated sodium silicate gel, which is smaller in size than the hydrated calcium silicate produced by cement hydration and can effectively fill the pores of the hardened slurry and improve the strength. The reaction is as follows: Na + + OH — = NaOH; 2NaOH + SiO2 = Na2SiO3 + H2O; (2) H2PO3 — Reaction with Al2O3 in muddy fine sand The mineral components of muddy fine sand mainly include quartz, calcite, dolomite, calcite, etc. In a strong alkaline environment, Al2O3 in muddy fine sand hydrolyzes to produce Al(OH)3; aminotrimethylenephosphonic acid pentasodium hydrolysis produces H2PO3 —It undergoes polymerization reaction with Al(OH)3 and forms gas-hardening binders aluminum dihydrogen phosphate and aluminum monohydrogen phosphate, which undergo violent neutralization reaction with the alkaline substance Ca(OH)2 produced by cement hydration, increase the solidification speed of cement paste, form a dense hardened structure, and promote the coagulation and hardening of the paste; the reaction is as follows: Al2O3 + 3H2O = 2Al(OH)3; Al(OH)3 + 3H3PO4 = Al(H2PO4) + 3H2O; 2Al(OH)3 + 3H3PO4 = Al2(HPO4)3 + 6H2O; Al(OH)3 + H3PO4 = AlPO4 + 3H2O; (3) Complexation reaction
[0021] Under alkaline conditions, complexation reaction occurs, and the inorganic ligands in the cement paste have OH - It is easy to combine with phosphate ions and will preferentially combine with hard acid Ca as the central ion. 2+ Combined to form a hydroxy complex ion. The phosphonic acid group produced by the hydrolysis of aminotrimethylenephosphonic acid sodium and the carboxyl group produced by the hydrolysis of etidronic acid disodium are mostly active group substances containing lone pairs of electrons. They are typical electron donors and can react with alkali metal ions Ca 2+ Form a stable complex. 3. Mechanism of action of ethyl trimethylsilyl acetate
[0022] (1) Hydrolysis of ethyl trimethylsilyl acetate (2) Hydrolysis of sodium aminotrimethylene phosphate (3) The amino group and methylene chain produced by the hydrolysis of sodium aminotrimethylene phosphate react with the ethyl silicate group produced by the hydrolysis of ethyl trimethylsilyl acetate to generate ethyl orthosilicate groups. The reaction is as follows: The ethyl ester group undergoes polymerization to form polyethyl silicate, the reaction is as follows: The ethyl silicate groups form a network structure, filling the pores of the hardened cement paste and improving the paste strength and impermeability.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The technical solution of the present application uses mud-containing fine sand as the main raw material, cement and slag as auxiliary materials, and trimethylsilyl acetate, disodium hydroxyethyl phosphonate and pentasodium aminotrimethylene phosphate as additives. The clay mineral content in the mud-containing fine sand is relatively high, and it has good water absorption and expansion properties, and the clay particle size is fine, and the specific surface area of the soil particles per unit mass is large, so it has strong adsorption capacity and ion exchange capacity, which can effectively improve the viscosity of the synchronous grouting material and the slurry stability; at the same time, the fine sand particles play a skeleton role in the synchronous grouting material, increasing the strength of the slurry consolidation body; by adding trimethylsilyl acetate to react with each component, the impermeability and strength of the synchronous grouting material can be effectively improved; the addition of disodium hydroxyethyl phosphonate effectively improves the flowability and early strength of the synchronous grouting material; the addition of pentasodium aminotrimethylene phosphate effectively improves the compressive strength of the synchronous grouting material and shortens the setting time of the slurry.
[0024] The technical solution of the present invention also has the following advantages: (1) The present invention realizes the utilization of large-volume muddy siltstone shield slag, with the slag component dosage reaching 60%. Compared with traditional synchronous grouting materials, it can achieve zero addition of fly ash, bentonite and fine sand, and at the same time reduce cement usage by 50%, reduce material costs by about 71%, and also reduce a large amount of slag transportation and disposal costs, thereby increasing the added value of slag utilization and achieving significant overall economic benefits; (2) The compounded admixture can greatly improve the anti-seepage ability of the slurry, reduce the setting time of the slurry, and increase the compressive strength of the slurry; at the same time, it can improve the flowability of the slurry. During the storage and transportation process, the slurry can maintain a certain workability, uniformity and good construction performance. After the slurry is injected into the shield tail through the pipeline, it can fill the gap between the pipe segment and the surrounding rock more fully; (3) The shield slag slurry making process adopted by the present invention is simple, has high production efficiency, and occupies a small area of equipment, and can be adapted to small urban subway construction sites.
[0025] (4) The present invention is a green and environmentally friendly synchronous grouting material, which can turn slag into treasure, reduce environmental pollution caused by slag transportation and discharge, reduce natural sand and gravel mining, and reduce secondary pollution and carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figures are test diagrams of the fluidity of the synchronous grouting materials of Example 3 and Comparative Example 2; wherein Figure A is the test diagram of Example 3, and Figure B is the test diagram of Comparative Example 2; Figure 2 The 28d compressive strength test diagrams of the synchronous grouting materials of Example 3 and Comparative Example 1 are shown in Figure A; wherein Figure A is the test diagram of Example 3, and Figure B is the test diagram of Comparative Example 2; Figure 3The 28d compressive strength test diagrams of the synchronous grouting materials of Example 3 and Comparative Example 2 are shown in Figure A; Figure A is the test diagram of Example 3, and Figure B is the test diagram of Comparative Example 2; Figure 4 28d compressive strength test diagrams of synchronous grouting materials of Example 3 and Comparative Example 4; wherein, Figure A is the test diagram of Example 3, and Figure B is the test diagram of Comparative Example 4; Figure 5 It is a measurement diagram of the setting time of the synchronous grouting materials of Examples 1, 2 and Comparative Example 3; wherein, Figure A is the detection diagram of Example 1, Figure B is the detection diagram of Example 2, and Figure C is the detection diagram of Comparative Example 3. DETAILED DESCRIPTION
[0027] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0029] Some of the raw materials used in the following examples and comparative examples of the present invention are as follows: Cement: ordinary Portland cement; Slag: density is 2.89g / cm 3 , with a specific surface area of 422.3m 2 / kg; Ethyl trimethylsilyl acetate (C7H 16 O2Si, CAS No.: 4071-88-9), density 0.876 g / mL, specific gravity 0.876; Etidronate disodium (C2H9NaO7P2, CAS No.: 7414-82-7); Pentasodium aminotrimethylene phosphate (C3H7NNa5O9P3, CAS No.: 2235-43-0); The fine sand containing mud is obtained by using shield slag as raw material and screening multiple times, as follows: (1) The shield slag is transported into the slag pool by dump trucks, loaded by excavators and other means, and enters the primary screening system through the silo; (2) The coarse particles larger than 6 mm and the sandy mud smaller than 6 mm are separated by screening with a double-layer shaftless roller screen. The screened coarse particles are transported to the coarse particle storage area by a conveyor belt; (3) The sand-containing mud with a size of less than 6 mm obtained in step (2) is washed and then enters a secondary screening system, and a vibrating screening machine is used to separate the intermediate particles of 2-6 mm and the sand-containing mud with a size of less than 2 mm, and the intermediate particles are transported to a designated stacking area; (4) The sand-containing mud with a size of less than 2 mm obtained in step (3) is separated into fine sand and mud containing mud by a cyclone, and the fine sand containing mud is collected; the mud is separated into mud cake and clear water by a filter press; The mud-containing fine sand obtained after screening has a clay content of 20-30wt%. Example 1
[0030] A synchronous grouting material based on muddy silt shield slag, comprising the following components in parts by weight: 16 parts cement 16 parts slag 147 parts of fine sand containing mud 67 parts water 0.03 parts of ethyl trimethylsilyl acetate Etidronate disodium 0.07 parts 0.03 parts of pentasodium aminotrimethylene phosphate; The preparation method comprises the following steps: S1. First, mix cement, slag, fine sand containing mud powder and water (40 parts) and stir them thoroughly for 2 minutes; S2, then mix ethyl trimethylsilyl acetate and water (7 parts) and add to the above mixture and stir thoroughly for 1 minute; S3, then mix etidronate disodium with water (12 parts) and add to the above mixture and stir thoroughly for 2 minutes; S4. Finally, mix pentasodium aminotrimethylenephosphonate and water (8 parts) and add to the above mixture and stir thoroughly for 2 minutes to obtain synchronous grouting material. The whole stirring time should be controlled within 6 to 8 minutes. Example 2
[0031] The composition and proportion of each raw material in this example are shown in Table 1, and the preparation method is the same as that in Example 1. Example 3
[0032] The composition and proportion of each raw material in this example are shown in Table 1, and the preparation method is the same as that in Example 1.
[0033] Table 1 Raw material composition and proportion of Examples 1-3 (unit: part) Comparative Example 1
[0034] The raw material composition and proportion of this comparative example are shown in Table 2, and the preparation method is as follows: Use an excavator or forklift to transport the muddy and fine sand to a twin-shaft forced mixer, add water and stir for 1 minute, transport cement and slag to the mixer through storage tanks and mix them fully with the muddy and fine sand (both are equipped with automatic weighing systems) for 2 minutes, then add early strength agent and polycarboxylic acid high-efficiency water reducing agent, and continue stirring. The entire mixing process should be controlled within 6-8 minutes. Comparative Example 2
[0035] The raw material composition and proportion of this comparative example are shown in Table 2, and the preparation method is the same as that of comparative example 1. Comparative Example 3
[0036] The raw material composition and proportion of this comparative example are shown in Table 2, and the preparation method is the same as that of comparative example 1. Comparative Example 4
[0037] The raw material composition and proportion of this comparative example are shown in Table 2, and the preparation method is the same as that of comparative example 1.
[0038] Table 2 Raw material composition and proportion of comparative examples 1-4 (unit: part)
[0039] The synchronous grouting materials obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to relevant performance tests, as follows: The setting time test method refers to the relevant provisions of the current industry standard "Standard for Test Methods of Basic Properties of Building Mortar" (JGJ / T70-2009); The fluidity test method refers to the provisions of the truncated cone fluidity test in the current national standard "Technical Specifications for Application of Cement-based Grouting Materials" (GB / T50448-2015); The compressive strength test method refers to the provisions of the unconfined compressive strength test in the current industry standard "Cement-Soil Mix Design Code" (JGJ / T 233-2011); The test methods for impermeability pressure and impermeability grade refer to the relevant provisions of "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009) and "Premixed Mortar" (GB / T 25181-2019).
[0040] The relevant test results are shown in Table 3 and Figure 1-Figure 5 shown.
[0041] Table 3 Test results of grouting material properties of Examples 1-3 and Comparative Examples 1-4
[0042] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0043] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A synchronous grouting material based on muddy silt shield slag, characterized in that: By weight, it includes the following components: 13-16 parts cement 16-20 parts of slag 142-147 parts of fine sand containing mud 0.03-0.1 part of trimethylsilyl acetate Etidronate disodium 0.07-0.17 parts Pentasodium aminotrimethylenephosphonate 0.03-0.1 parts 63-67 parts of water; The mud-containing fine sand is obtained after shield slag is screened multiple times.
2. The synchronous grouting material based on muddy silt shield slag according to claim 1 is characterized in that: The cement is ordinary Portland cement and / or sulphoaluminate cement.
3. The synchronous grouting material based on muddy silt shield slag according to claim 1 is characterized in that: The density of the slag is 2.0-3.0 g / cm 3 ; Specific surface area is 350-500m 2 / kg.
4. The synchronous grouting material based on muddy silt shield slag according to claim 1 is characterized in that: The particle size of the mud-containing fine sand is less than 2 mm, and the clay content is 20-30%.
5. The synchronous grouting material based on muddy silt shield slag according to claim 1 is characterized in that: The mud-containing fine sand is particles with a particle size of less than 2 mm obtained after shield slag is screened multiple times.
6. The synchronous grouting material based on muddy silt shield slag according to claim 5 is characterized in that: The screening of the mud-containing fine sand comprises the following steps: The shield slag is screened once to separate coarse particles larger than 6 mm and sandy mud smaller than 6 mm. The sandy mud smaller than 6 mm is then washed and screened twice to separate intermediate particles of 2-6 mm and sandy mud smaller than 2 mm. The sandy mud smaller than 2 mm is separated to obtain mud-containing fine sand and mud, and the mud-containing fine sand is collected.
7. The method for preparing synchronous grouting material based on muddy silt shield slag according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) First, cement, slag, mud-containing fine sand and part of water are mixed and stirred thoroughly to obtain a first slurry; (2) then mixing ethyl trimethylsilyl acetate with a portion of water and adding the mixture to the first slurry obtained in step (1), stirring the mixture thoroughly to obtain a second slurry; (3) mixing etidronate disodium with a portion of water and adding the mixture to the second slurry obtained in step (2) above, and stirring the mixture thoroughly to obtain a third slurry; (4) finally, pentasodium aminotrimethylenephosphonate and the remaining water are mixed and added to the third slurry obtained in the above step (3), and stirred thoroughly to obtain a synchronous grouting material; The entire stirring time of steps (1) to (4) is controlled within 5-10 minutes.
8. The method for preparing synchronous grouting material based on muddy silt shield slag according to claim 7, characterized in that: The entire stirring time is controlled at 6-8 minutes.
Citation Information
Patent Citations
Method of utilizing waste slurry and waste sand of slurry shield to prepare backfill grouting material
CN108409227A
Synchronous mortar prepared from shield muck slurry and preparation method
CN112723823A
Phosphorus-based low-pressure boiler treating agent and preparation method thereof
CN112811618A
Plastic early strength type shield tunnel synchronous grouting material and preparation method thereof
CN115583827A
Fire-resistant electromagnetic wave shield board
JP2000016857A
Cited By
High-performance environment-friendly synchronous grouting material and preparation method thereof
CN119797868A
A high-performance environmentally friendly synchronous grouting material and its preparation method
CN119797868B